Strengthening ADR System in Indonesia: Learning from ADR Practices in Hungary - Saputra, Beny (Indonesian Comparative Law Review, 2024)
Integrating Alternative Dispute Resolution (ADR) into legal systems is essential for improving access to justice, decreasing litigation expenses, and promoting enforced outcomes. This article examines the ADR practices in Hungary, a country that has successfully integrated ADR into its legal system, to gain significant insights for Indonesia, as both countries share the same sociocultural practices for communal dispute resolution. This normative legal research examines Hungary's extensive legal framework, the roles of institutional support structures, and the enforcement of ADR awards. The study employs comparative analysis that systematically evaluates pertinent legal documents, institutional reports, and scholarly literature from Hungary and Indonesia. The study found fundamental factors that contribute to the effectiveness of alternative dispute resolution (ADR) in Hungary including the existence of a clearly established legislative framework, sufficient institutional infrastructure, and effective regulation to enforce ADR decisions. Indonesia can adopt these techniques to improve its Alternative Dispute Resolution (ADR) system, resulting in more streamlined, cost-efficient, and fair processes for resolving disputes and to establish a more unified and efficient ADR system.